Abdominal myosteatosis is independently associated with hyperinsulinemia and insulin resistance among older men without diabetes. (29th May 2013) - Miljkovic, Iva; Cauley, Jane A.; Wang, Patty Y.; Holton, Kathleen F.; Lee, Christine G.; Sheu, Yahtyng; Barrett‐Connor, Elizabeth; Hoffman, Andrew R.; Lewis, Cora B.; Orwoll, Eric S.; Stefanick, Marcia L.; Strotmeyer, Elsa S.; et al.
<x xml:space="preserve">Abstract</x> Objective Skeletal muscle adipose tissue (AT) infiltration (myosteatosis) increases with aging and may contribute to the development of Type 2 diabetes mellitus (T2DM). It remains unclear if myosteatosis is associated to glucose and insulin homeostasis independent of total and central adiposity. Design and Methods The association between intermuscular AT (IMAT) in the abdominal skeletal muscles (total, paraspinal, and psoas) and fasting serum glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA‐IR) in 393 nondiabetic Caucasian men aged 65+ was evaluated. Abdominal IMAT, visceral AT (VAT), and subcutaneous AT (SAT) (cm3) were measured by quantitative computed tomography at the L4‐L5 intervertebral space. Results In age, study site, height, and muscle volume adjusted regression analyses, total abdominal and psoas (but not paraspinal) IMAT were positively associated with glucose, insulin, and HOMA‐IR (all P < 0.003). The associations between total abdominal and psoas IMAT and insulin and HOMA‐IR remained significant after further adjusting for lifestyle factors, as well as duel‐energy x‐ray absorptiometry (DXA) measured total body fat, VAT, or SAT in separate models (all P < 0.009). Conclusions A previously unreported, independent association between abdominal myosteatosis and hyperinsulinemia and insulin resistance among older Caucasian men was indicated. These associations may be specific for particular abdominal muscle depots, illustrating the potential importance of separately studying specific muscle groups.